Calcium and strontium salts of (glycinato‐κ2N, O)oxidobis(peroxido‐κ2O, O′)vanadate(V) tetrahydrate. (15th December 2013) - Higuchi, Takeshi; Uchida, Ayana; Hashimoto, Masato
<x xml:space="preserve">Abstract</x> The title salts calcium (glycinato‐κ2N, O)oxidobis(peroxido‐κ2O, O′)vanadate(V) tetrahydrate, Ca[VO(O2)2(NH2CH2COO)]·4H2O, and strontium (glycinato‐κ2N, O)oxidobis(peroxido‐κ2O, O′)vanadate(V) tetrahydrate, Sr[VO(O2)2(NH2CH2COO)]·4H2O, crystallized at pH ca 7.4 with similar lattice parameters. The glycinate anion acts as a bidentate N, O‐chelating ligand, and the V atom has a pentagonal bipyramidal geometry, with two η2‐peroxo groups and the glycinate N atom in the equatorial plane, and one terminal oxo and a glycinate O atom at the axial positions. The H atoms of three of the four water molecules in the strontium salt exhibited disorder over three positions for each molecule.